Azacitidine in the 'real‐world': an evaluation of 1101 higher‐risk myelodysplastic syndrome/low blast count acute myeloid leukaemia patients in Ontario, Canada. (16th May 2018) - Mozessohn, Lee; Cheung, Matthew C.; Fallahpour, Saber; Gill, Tripat; Maloul, Asmaa; Zhang, Liying; Lau, Olivia; Buckstein, Rena
Summary: The outcome of myelodysplastic syndrome (MDS) patients with uniformly higher‐risk disease treated with azacitidine (AZA) in the 'real‐world' remains largely unknown. We evaluated 1101 consecutive higher‐risk MDS patients (International Prognostic Scoring System intermediate‐2/high) and low‐blast count acute myeloid leukaemia (AML; 21–30% blasts) patients treated in Ontario, Canada. By dosing schedule, 24·7% received AZA for seven consecutive days, 12·4% for six consecutive days and 62·9% by 5‐2‐2. Overall, median number of cycles was 6 (range 1–67) and 8 (range 6–14) when restricted to the 692 (63%) patients who received at least 4 cycles. The actuarial median survival was 11·6 months [95% confidence interval (CI) 10·7–12·4) for the entire cohort and 18·0 months (landmark analysis; 95% CI 16·6–19·1 months) for those receiving at least 4 cycles. There was no difference in overall survival (OS) between the 3 dosing schedules ( P  = 0·87). In our large 'real‐world' evaluation of AZA in higher‐risk MDS/low‐blast count AML, we demonstrated a lower than expected OS. Reassuringly, survival did not differ by dosing schedules. The OS was higher in the 2/3 of patients who received at least 4 cycles of treatment, reinforcing the necessity of sustained administration until therapeutic benefits are realised. This represents the largest 'real‐world' evaluation of AZA in higher‐risk MDS/low‐blast count AML.